The Effect of Capital Structure, Liquidity, Company Size, and Inventory Turnover on Profitability - Fida Isti Qur’ani; Eny Purwaningsih (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
One indicator of a company's financial position is the company's Profitability. In this case, Profitability is more vital than profit or profit because high profits are not because a firm size has been doing work efficiently. In addition, industries that have high profits can more easily find investors who invest in developing their businesses. On the other hand, low Profitability makes it difficult for companies to get investors. Therefore, Profitability affects a company's survival, so the aim of this research is to empirically understand the effect of capital structure, liquidity, firm size, and inventory turnover on Profitability either partially or simultaneously in manufacturing companies in various industrial sectors listed on the BEI. During 2018-2020. The implementation of this research uses a type of causal research to understand the relationship between cause and effect on two or more variables. The sample in the implementation of this research is the various industrial sector manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020 through the purposive sampling method. 13 companies meet the research sample criteria, so the sample is 39 financial reporting. This research method uses multiple regression analysis. The research results indicate a significant effect of the liquidity variable (Current Ratio) and firm size variable (Firm Size) on Profitability. At the same time, the variables of capital structure (Debt to Equity Ratio) and inventory turnover (Inventory Turnover Ratio) do not significantly affect Profitability. Simultaneously there is the influence of the variables of capital structure (Debt to Equity Ratio), liquidity (Current Ratio), firm size (Firm Size), and inventory turnover (Inventory Turnover Ratio) on Profitability.